REAKSI PASAR MODAL TERHADAP PENGUMUMAN KEMENANGAN PRESIDEN JOKO WIDODO BERDASARKAN KEPUTUSAN KPU PEMILU PERIODE 2019-2024 (Studi pada Perusahaan BUMN yang Terdaftar Di BEI) - Akbar, Erica P.; Saerang, Ivonne S.; Maramis, Joubert B. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
The capital market is one indicator of economic progress. Events affect the formation of stock price fluctuations. This research was conducted with the aim of knowing the Market Reaction to the announcement of victory, based on data on stock price movements 14 days before and after the event. This type of research is in the form of quantitative research using secondary data, returns and volume of share prices of SOE companies going public, then tested different paired samples test. The results showed that there were significant differences in Abnormal Return. That is, the market reacts to the Announcement of Victory, because stock price movements are still influenced by an information and events. Meanwhile, TVA Abnormal Indicator shows a unique result, there is no partial difference in abnormal trading activity but there is a significant difference in the combined ATVA test. Investors in SOE shares trust the value of SOE shares so that they are not easily affected by short-term information. However, in SOE stock transactions (combined TVA Abnormal Test), a fraction of the activities of panicked SOE Investor investors, as well as traders' activities, can be seen, so there are significant differences in the average Investor trading activityKeywords:Â Event Study, Abnormal Return, and Abnormal TVA